Upregulation of HLA class II, but not intercellular adhesion molecule 1 (ICAM-1) by granulocyte-macrophage colony stimulating factor (GM-CSF) or interleukin-3 (IL-3) in synergy with dexamethasone. - Sadeghi, R; Feldmann, M; Hawrylowicz, C (1992)
In this study we have compared the effects of granulocyte macrophage colony stimulating factor (GM-CSF) on purified normal blood monocytes, with two other haemopoietic growth factors, Interleukin (IL-) 3 and Macrophage (M-)CSF on HLA class I, class II and intercellular adhesion molecule 1 (ICAM-1) expression in the presence and absence of dexamethasone (Dex). IL-3 alone, like GM-CSF, was a weak inducer of HLA class II expression but in combination with Dex markedly enhanced HLA-DR, DP and DQ expression. Similar changes were observed for HLA class I expression. The response to both IL-3 and GM-CSF was not additive in the presence of an optimal concentration of one cytokine and titrating concentrations of the other indicating that they may use common receptors and signal transduction mechanisms. Although IL-3 or GM-CSF alone also enhanced ICAM-1 expression, Dex inhibited both constitutive and the cytokine induced expression of this antigen. In contrast M-CSF, in the presence or absence of Dex, failed to enhance ICAM-1, HLA class I or II expression. These observations further highlight differences between the effects of the haemopoietic growth factors GM-CSF and IL-3 versus M-CSF in the regulation of monocyte function. Finally, the distinct effect of a combination of glucocorticoids with GM-CSF or IL-3 to induce high levels of HLA expression on human monocytes suggests they may have an important role during inflammatory conditions in vivo.